2016
DOI: 10.1016/j.prosdent.2015.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cement-retained versus screw-retained implant-supported restorations for marginal bone loss

Abstract: The current meta-analysis indicated that cement-retained, fixed implant-supported restorations showed less marginal bone loss than screw-retained, fixed implant-supported restorations during the follow-up period, which ranged from 12 to 180 months. However, the small difference between the mean values may not show clinical significance. The rates of prosthetic complication and implant survival also compared favorably with cement-retained prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
104
3
27

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 140 publications
(142 citation statements)
references
References 44 publications
8
104
3
27
Order By: Relevance
“…For example, it has been proposed that the screw access hole helps to transfer stress off the long axis of the implant, and that different restorative materials can transfer occlusal loads laterally to the implant instead of axially (7). The cement also may be better at filling discrepancies, absorbing and equalizing the stress of deformations caused by contact between the abutment and implant in the prosthesis structure (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, it has been proposed that the screw access hole helps to transfer stress off the long axis of the implant, and that different restorative materials can transfer occlusal loads laterally to the implant instead of axially (7). The cement also may be better at filling discrepancies, absorbing and equalizing the stress of deformations caused by contact between the abutment and implant in the prosthesis structure (16).…”
Section: Discussionmentioning
confidence: 99%
“…These factors can contribute to fixation screw of screwed prosthesis present stress overload in the structure, which contributes to greater complication rates can explain the frequent failures (e.g. screw loosening or fracture) that are observed in screwed prostheses (7,15,17). The high risk in the screw-retained prosthesis can be related to lower preload in the screw with displacement (penetration and gaps) higher and concentrated on the threads of the screw/or abutment when compared to cement-retained (15).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, cemented crowns were simulated in this study because they exhibit better biomechanical behavior with Morse taper implants [16] and contribute to greater preservation of the bone tissue, compared with the screwed crown [22]. …”
Section: Discussionmentioning
confidence: 99%
“…In the static load test, vertical load testing showed that both the chamfer and shoulder models had damage at the zirconia margin, while no marginal damage was seen in any group with the slanting load test at an angle of 30°1 7,19,23) . However, the slanting load caused separation at the border between the zirconia sleeve and the titanium base in the samples with the shoulder margin.…”
Section: Discussionmentioning
confidence: 89%
“…The aim of implant treatment is now not only to restore masticatory function, but also to recover esthetics 5,6) . As patient demand for better tooth esthetics has increased, the most common fixation between fixture and superstructure changed from screw retention to cement retention 7) . The screw-retention system has limitation on clinical application in esthetic regions of the maxillary anterior teeth and mandibular premolars, because the screw holes disturb the appearance.…”
Section: Introductionmentioning
confidence: 99%